Framework of decision making process for variation works to analyse impacts caused by factors influencing decisions - Othman, Norazam (2016)
Standard forms of contract provide guidelines in managing variations to construction projects. However, problems exist as there are factors influencing construction professionals in the decision making process. Thus the specific objectives of this study are to identify and establish the decision making process for variation works, to determine the factors that influences construction professionals in the decision making, to identify and establish the best practice for developing a conceptual framework of decision making process and to develop a framework of decision making process for variation works that is able to analyze the impacts caused by these factors. The literature review suggested that there are factors such as standard forms of contract, practice, professionals and institutions, client and employers, contractors, other construction professionals, experience and knowledge acquisition and procurement system that influences construction professionals during the decision making process. Available framework of decision making lack the methodological assessment of these factors influencing decisions on variations which is needed to embrace positive changes and mitigate negative changes effectively. Data of the study consist of 18 construction professionals and the transcripts of the interview were exported into computer software to quantify the data, manage and find out the pattern of their responses to the questionnaire. The data analysis showed that the impact caused by the factors influencing decisions on variation can be analysed to determine whether it give a positive, negative or neutral impacts. The score sheet provided the methodological assessment in the conceptual framework taking into consideration best practices of the decision making process. The developed framework of decision making process was validated by construction industry’s expert to consolidate its criteria of comprehensiveness, reliability, practicality and adaptability. The findings of the study shows that the developed framework are able to improve on the decision made by providing a methodological assessment of these factors influencing decisions on variations.